Pelvi-Ureteric Junction Obstruction In A Malrotated Ectopic Kidney With Concomitant Lithiasis – A Rare Clinical Scenario - Siddiqui, Mohammed Ayub; Sharma, Shashank; Shaw, Vivek (Journal of Society of Surgeons of Nepal, 2023)
Kidney lying outside renal fossa is referred as ectopic kidney. Hereby we are presenting a rare case of Pelviureteric junction obstruction in a malrotated ectopic kidney with concomitant lithiasis in a 16 year male. He presented with pain in lower abdomen intermittently. On CT scan, a left malrotated ectopic kidney was located in the pelvis near the midline with a 10 mm stone in the lower pole, and having obstructed pattern drainage with moderate hydronephrosis. Open Anderson-Hynes dismembered pyeloplasty was done. Thorough clinical approach with delineating aberrant anatomy of ectopic kidneys and their vascular supply with consideration of unusual functional data on conventional functional renogram is necessary for intervening in malrotated ectopic kidney with concomitant lithiasis.